Poesía y poliorcética. El Auto de San Lorenzo de José de Anchieta y la conquista del imaginario indígena - Suárez, Juan Carlos Cruz (Diálogos Latinoamericanos, 2013)
Abstract The conquest and colonization of a territory entails a series of operations designed to eliminate a whole model of culture. After wartime, the colonization and subsequent disposal of the collective imagination of the conquered space is imposed by the invadors. The operations performed in order to carry out such a removal occur mainly in the space of discourse. Indeed poetry —or literature in general— is one of the discourses used to execute this operation. This article aims to establish a connection between the art of war and the colonization of the imagination through poetry. I will try to point out that the two mechanisms of invasion cannot be separated if the aim is to control the other effectively. Following this perspective I will analyze El auto de San Lorenzo written in Brazil in the middle of the XVI century by the Jesuit José de Anchieta. This play is precisely one of the most representative evidences of what I will call here a total conquest.